Evaluation of efficacy of NIBRG-14 vaccine against highly pathogenic H5N1 viruses isolated during 2011 influenza outbreaks in Vietnam - Huy Tung, Dau; Van Quyen, Dong; Tung, Nguyen; Xuan Hanh, Tran; Young Bong, Kim; Duy Khang, Dinh (Vietnam Journal of Science and Technology, 2017)
Highly pathogenic avian influenza (HPAI) H5N1 viruses continue to be endemic in many Asian countries causing lethal infections in human. The vaccine virus (NIBRG-14) developed from a H5N1 virus strain (A/Vietnam/1194/2004) has been approved by WHO for use in human as well as poultry vaccine. It is well-known that the A/H5N1 viruses have diversified both genetically and antigenically allowing them to escape from the host immune surveillance system. Therefore, evaluation of the vaccine immunogenicity and its relationship to newly emerging viruses is crucially important. NIBRG-14 virus particles propagated in embryonated chicken eggs were inactivated with formalin and adjuvanted with mineral oil to form a water-in-oil emulsion. The resulting vaccine was injected subcutaneously into chickens and ducks. The vaccinated birds were challenged with the HPAI virus strains circulating in Vietnam including clade 1, clade 2.3.2.1a and 2.3.2.1b at day 21 post-vaccination (p. v.). We observed that vaccinated birds were protected from manifestation of disease signs upon challenge with HPAI clade 1 and clade 2.3.2.1a viruses; however, it did not confer protection against clade 2.3.2.1b challenge andstressing the need for development of new effective vaccines against the newly emerging viruses.